2021
DOI: 10.1021/acscatal.1c01506
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Engineered Metal–Organic Frameworks for Electrochemical Reduction of Carbon Dioxide to Carbon Monoxide

Abstract: The economic feasibility of electrocatalytic carbon dioxide reduction reaction (CO2RR) relies on developing highly selective and efficient catalysts operating at a high current density. Herein, we explore a ligand-engineering strategy involving the use of metal–organic frameworks (MOFs) and combining the desirable features of homogeneous and heterogeneous catalysts for boosting the activity of CO2RR. Zn-based MOFs involving two different azolate functional ligands, i.e., 1,2,4-triazole (Calgary Framework 20, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 46 publications
0
64
0
Order By: Relevance
“…Recently, porous crystalline covalent organic frameworks (COFs) have attracted extensive attention in many fields including gas storage, catalysis, and photoelectric areas because of their well-defined tailorable chemical and pore structures and large specific surface areas. 32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, porous crystalline covalent organic frameworks (COFs) have attracted extensive attention in many fields including gas storage, catalysis, and photoelectric areas because of their well-defined tailorable chemical and pore structures and large specific surface areas. 32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…A desired electrocatalyst should have a high TON, a high TOF, and low overpotential (Zhang H. et al, 2021). The Zn-based MOF CALF20 demonstrates the highest CO Faradaic efficiency of 94.5% at −0.97 V vs. RHE with a TOF of 1360.8 h −1 and a partial current density of −32.8 mA/cm 2 for electrochemical CO 2 R to CO (Al-Attas et al, 2021). The redox-active In-MOF shows the first example of an Ni-based MOF catalyst in electrocatalytic CO 2 R, which suggests new prospects for designing novel and efficient non-noble, metal-based, redox-active, biomimetic MOFs (Zhou et al, 2021).…”
Section: Co 2 and Methanementioning
confidence: 99%
“…Adjusting organic linkers to regulate the selectivity of eCO 2 RR is a novel strategy in catalyst design. [ 12,16,17 ] Al‐Attas et al. have introduced the 1,2,4‐triazolate group into zeolitic imidazolate framework‐8 (ZIF‐8) to replace the 2‐methylimidazolate group, increasing CO selectivity from 61% to 94%.…”
Section: Introductionmentioning
confidence: 99%